MANAJEMEN RISIKO CUACA HUJAN DALAM PROYEK KONSTRUKSI BANGUNAN GEDUNG BERDASARKAN ANALISIS DATA DI KALIMANTAN SELATAN - Widiastuti, Endah; Karim, Abdul; Yuliana, Candra (Jurnal Infrastruktur, 2026)
The rainy season in South Kalimantan is characterized by high intensity and unpredictable patterns, posing significant risks to the success of building construction projects. These risks include material damage, reduced labor productivity, schedule delays, and increased project costs. This study aims to identify, analyze, and formulate mitigation strategies for risks caused by rainfall in construction projects within the region. Primary data were collected through questionnaires distributed to 30 respondents consisting of contractors, construction managers, and supervisory consultants, while secondary data were obtained from literature and project documents. The analysis involved validity and reliability testing of the instruments using SPSS, followed by the Severity Index method to measure the probability and impact of risks, and the Probability Impact Matrix to determine dominant risk levels. The results indicate that 25 risks factors were valid and reliable, with Cronbach’s Alpha values exceeding 0.9. The analysis identified seven high-risk variables, namely delays in material delivery, material damage due to humidity, decreased labor productivity, postponement of concrete casting, rescheduling of project activities, delays in managerial decision-making, and unexpected additional costs. Proposed mitigation strategies include contingency planning for logistics, material protection measures, flexible work scheduling, the application of adaptive construction technologies, and strengthened managerial coordination. These findings are expected to contribute to enhancing the resilience of construction projects against extreme weather conditions and serve as a foundation for developing adaptive risk management practices in Indonesia’s construction sector.